Implementasi sistem ERP (Enterprise Resource Planning) menggunakan odoo versi 14 (studi pada proses pengadaan barang di PT RM) - Rahman Maulana; Nono Heryana; Apriade Voutama (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System, 2022)
PT RM merupakan perusahaan yang bergerak dibidang trading mobil, proses pengadaan barang dalam perusahaan trading mobil merupakan faktor utama dalam terlaksananya proses trading. Namun, dalam proses pengadaan barang di perusahaan trading mobil ini masih terhambat dalam pencatatan yang masih tradisional dan tidak terintegrasi. Dan penelitian ini memiliki tujuan untuk mencegah fraud dari karyawan yang tidak memiliki integritas. Oleh karena itu, sistem ERP (Enterprise Resource Planning) menjadi solusi untuk permasalahan pencatatan yang masih tradisional dan tidak terintegrasi. Odoo merupakan sistem ERP yang open-source dan user friendly. Odoo memiliki beberapa versi yang mana setiap versi memiliki plus dan minus nya masing-masing akan tetapi Odoo dengan versi angka terbesar adalah Odoo yang paling update. Oleh karena itu, implementasi sistem ERP (Enterprise Resource Planning) ini menggunakan Odoo versi 14. Abstract: The development of information technology is an important factor for a trading company to develop a business or business [1]. The purpose of this research is to change the system of recording the procurement of goods at PT RM (initials of company name) which is still traditional to be more modern and integrated using technology that developed, namely the ERP system (Odoo version 14), of which Odoo version 14 is an open-source / free ERP system service. And to prevent fraud or fraud. Business Process Identification, Master Data Identification, Data Analysis. This type of research uses a qualitative approach that will produce theories and conclusions about the recording of procurement of goods in a modern and integrated manner, theories and conclusions will be submitted to the object of research to be applied in the company. The discussion and results contain the input of several components to support the implementation of the odoo system14 and produce records that can be used by the research object company. The results of this research must be submitted to the object of research to change the recording of procurement of goods that are still traditional and not integrated to become more modern and integrated using information technology, namely the ERP system.